ОИЛАНИНГ ДЕМОГРАФИК РИВОЖЛАНИШИ - Утепова, Г.Б.; Отенов, Н.Т. (SCIENCE and SOCIETY, 2017)
Family is based on natural, biological relations, the marriage is based – on the kin, economical, legal, political relations. Family is a social group, connected with each other through marriage and responsibility.
Keywords: demographic situation; family; marriage; healty mothere; healty child; to break a marriage; stable families; demographic policy